2023
DOI: 10.1002/alr.23145
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic predictors of occult intracranial involvement in olfactory neuroblastoma patients

Abstract: BackgroundTraditional management of olfactory neuroblastoma (ONB) includes margin‐negative resection with removal of cribriform plate, dura, and olfactory bulb, regardless of intracranial disease. This approach may be overtreating certain patients. Our investigation examines risk factors associated with occult intracranial disease to optimize therapeutic outcomes.MethodsThis retrospective, multi‐institutional cohort study examined clinical covariates associated with occult intracranial involvement. Patient dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…3 Among the subjects who did not have imaging evidence of intracranial disease, those patients with advanced Hyams grade (III/IV) tumors were more likely to have occult disease (29%) as compared to those with low-grade (I/II) disease (4%). 3 Several other studies evaluated the success of extracranial ONB resection in patients whose preoperative imaging did not show evidence of skull base or intracranial involvement. Cai et al reported their experience with extracranial ONB resection in which 11 patients (one Kadish A, seven Kadish B, one Kadish C, and two Kadish D) had 100% overall survival (OS) and 87% diseasefree survival (DFS) at 5 years.…”
Section: Candidates For Extracranial Resection Onlymentioning
confidence: 94%
See 4 more Smart Citations
“…3 Among the subjects who did not have imaging evidence of intracranial disease, those patients with advanced Hyams grade (III/IV) tumors were more likely to have occult disease (29%) as compared to those with low-grade (I/II) disease (4%). 3 Several other studies evaluated the success of extracranial ONB resection in patients whose preoperative imaging did not show evidence of skull base or intracranial involvement. Cai et al reported their experience with extracranial ONB resection in which 11 patients (one Kadish A, seven Kadish B, one Kadish C, and two Kadish D) had 100% overall survival (OS) and 87% diseasefree survival (DFS) at 5 years.…”
Section: Candidates For Extracranial Resection Onlymentioning
confidence: 94%
“…For cases without obvious skull base involvement on imaging, a unilateral ONB resection including the dura and olfactory apparatus would capture any occult disease, estimated at 29% in grade III/IV and 4% in grade I/II tumors. 3 Small volume, low-grade tumors where midline dural margins can be easily cleared are best suited for this unilateral approach. The authors advocate against a completely extracranial ONB resection that preserves the cribriform plate, dura, and olfactory apparatus unless the tumor orig- inates from a region other than the olfactory cleft, leaving the skull base completely uninvolved (Figure 2).…”
Section: Extent Of Resectionmentioning
confidence: 99%
See 3 more Smart Citations